Las divergencias en el régimen verbal del objeto directo e indirecto en polaco y en castellano - Pawlik, Janusz (Studia Romanica Posnaniensia, 2007)
The divergence in the use of noun objects required by certain verbs in both languages is obvious. The problem, however, becomes difficult to solve, because in Spanish it is sometimes impossible to tell the difference between the direct and indirect object in a verb group. Unlike other Romance languages, the preposition ‘a’ is often both the mark of accusative and dative forms. In addition, the defective pronoun forms replacing noun objects are widespread in Spain (leísmo, laísmo) and create confusion in speakers’ minds. In this paper, we will try to find out the real syntactic value of some Spanish objects, usually mistaken by Polish learners of Spanish, and to draw up a list of those verbs whose objects don’t agree in both languages.